BAHASA INGGRIS DALAM IKLAN BUSANA MUSLIMAH PADA MAJALAH AULIA - Heriyanti, Rina (Fakultas Dakwah IAIN Purwokerto, 2013)
This paper discusses the use of English in the advertisement of muslim clothes in massmedia. Muslim clothes has been a part of modern life style and has taken different image as atraditional lifestyle to a modern one. Wearing muslimah cloth is no longer considered as oldfashioned but as a trendy and fashionable life style.The English language used in the advertisements of muslim cloth contains popularvocabulary. This paper discussed the linguistic accuracy of the use of words. This linguisticperspective indicates whether the advertisements follow the linguistic rules or go with theirown logics.The use of English in the advertisement has a benefit of indirect understanding of theadvertisement content because readers should think for some time about the meaning. It isdifferent from those totally written in Bahasa Indonesia, which tend to make the readers skipthe pages because they can directly understant the content of the advertisement.